2009
DOI: 10.2133/dmpk.24.500
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Drug-Drug Interactions based on Time-Dependent Inhibition from High Throughput Screening of Cytochrome P450 3A4 Inhibition

Abstract: A method of assessing the risk of drug-drug interaction (DDI) caused by mechanism-based inhibition (MBI) was developed for early-stage drug development using cytochrome P450 (CYP) 3A4 inhibition screening data. CYP3A4 inhibition was evaluated using a fluorescent substrate with or without preincubation containing an inhibitor. The results showed that five well-known mechanism-based inhibitors, but not the competitive inhibitor ketoconazole, had lower IC(50) after preincubation, suggesting the utility of the IC(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
(22 reference statements)
5
25
1
Order By: Relevance
“…The identity of reactive metabolites of ritonavir, however, remains unknown. Furthermore, the results of other studies argued against the mechanism-based CYP3A4 inhibition 9 or indicated that ritonavir acts as a competitive [10] or mixed competitive-noncompetitive inactivator of CYP3A4 [1113]. …”
Section: Interaction Of Cyp3a4 With Ritonavirmentioning
confidence: 99%
“…The identity of reactive metabolites of ritonavir, however, remains unknown. Furthermore, the results of other studies argued against the mechanism-based CYP3A4 inhibition 9 or indicated that ritonavir acts as a competitive [10] or mixed competitive-noncompetitive inactivator of CYP3A4 [1113]. …”
Section: Interaction Of Cyp3a4 With Ritonavirmentioning
confidence: 99%
“…Using [I] u /K i,u ratios-i.e., the unbound plasma concentration of the inhibitory metabolite, [I] u , divided by the equilibrium constant for inhibition of warfarin 7-hydroxylation in human liver (HL) microsomes (HLM), normalized to the amount of free inhibitor available in those microsomes, (K i,u )-we predicted the minor AMIO metabolite, N,Ndidesethylamiodarone (DDEA) to be the culprit most likely to induce the hypocoagulation effect seen when AMIO is coadministered with warfarin (McDonald et al, 2012). Of course, [I] u /K i,u ratios are most useful in predicting the inhibitor efficiency of purely reversible inhibitors, and there is conflicting evidence in the literature as to whether AMIO and/or its primary metabolite, N-monodesethylamiodarone (MDEA) can act as irreversible inhibitors of various P450 isozymes, including CYP2C9 (Ohyama et al, 2000;Obach et al, 2007;Berry and Zhao, 2008;Mori et al, 2009;Sekiguchi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, crude extracts of 78 herbal medicines that exhibit inhibitory effects on CYP3A4 and CYP2D6 were found to be involved in the metabolism of numerous synthetic drugs (Sekiguchi et al, 2009). This study found that rutaecarpine can inhibit the activities of several types of CYPs, namely CYP1A2, CYP2C9, CYP2C19 and CYP2E1, indicating that more than one metabolite of rutaecarpine can be generated in a multiple-oxidation reaction.…”
Section: Discussionmentioning
confidence: 99%